Содда кунед:
\((x+y+z)^3-(x+y-z)^3-(x-y+z)^3-(-x+y+z)^3\)
a=x+y ва b=x-y
\((x+y+z)^3-(x+y-z)^3-(x-y+z)^3-(-x+y+z)^3=\)
\(=((a+z)^3-(a-z)^3)-((b+z)^3+(-b+z)^3)=\)
\(=((a+z)^3-(a-z)^3)-((b+z)^3-(b-z)^3)\)
\((a+z)^3-(a-z)^3=(a+z-a+z)\cdot((a+z)^2+(a+z)(a-z)+(a-z)^2)=\)
\(=2z\cdot(a^2+z^2+a^2-z^2+a^2+z^2)=2z\cdot(3a^2-z^2)\)
\((b+z)^3-(b-z)^3=2z\cdot(3b^2-z^2)\)
\(((a+z)^3-(a-z)^3)-((b+z)^3-(b-z)^3)=\)
\(=2z\cdot(3a^2-z^2)-2z\cdot(3b^2-z^2)=\)
\(=2z\cdot(3a^2-z^2-3b^2+z^2)=2z\cdot(3a^2-3b^2)=\)
\(=6z\cdot(a^2-b^2)\)
\(a^2=x^2+2xy+y^2\)
\(b^2=x^2-2xy+y^2\)
\(a^2-b^2=x^2+2xy+y^2-(x^2-2xy+y^2)=\)
\(=4xy\)
\(6z\cdot(a^2-b^2)=6z\cdot4xy=\)
\(=24xyz\)
\((x+y+z)^3-(x+y-z)^3-(x-y+z)^3-(-x+y+z)^3=24xyz\)
Ҷавоб: 24xyz.